Penerapan Metode Pembelajaran Sentra Balok untuk Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Kelompok A1 RA Hidayatul Hikmah - wati, erna; Abidin, Ratno; Kurniawati, Tri (Universitas Muhammadiyah Surabaya, 2023)
The aim of this research is to apply the beam center learning method to improve the fine motor skills of early childhood group A1 RA Hidayatul Hikmah Lolawang. The beam center learning method can make the learning atmosphere more fun and enjoyable and children are able to develop their fine motor skills. =. Based on data analysis, it shows that the significance value of Sig. (2-tailed) is 0.000 < 0.05, so H0 is rejected and Ha is accepted, so it can be concluded that there is an average difference between pretest and posttest learning outcomes, which means there is an influence of the beam center learning method on children's fine motor skills. early age. It can be seen that the calculated t has a negative value of -15,289. The t-count has a negative value because the average pretest learning score is lower than the average posttest learning result so that the t-count becomes t-count 15.289 > t-table 2.000, which means that the basis for decision making is that H0 is rejected and Ha is accepted. , so it can be concluded that there is a difference between the pretest and posttest averages, which means that there is an influence of using the beam center learning method to improve the fine motor skills of young children